Penerapan teknologi pengolahan permen fungsional Lidah Buaya Pada Petani di Desa Argodadi, Sedayu, Bantul, DIY - Chatarina Wariyah; Riyanto Riyanto (Unri Conference Series: Community Engagement, 2021)
Argodadi village is located in Sedayu District, Bantul Regency, DIY. Its hilly and calcareous soil conditions and rice fields without technical irrigation lead to drought, therefore farmers initiated for planting of aloe vera. The Demangan Village Farmers community is one of the groups that cultivate aloe vera plants. They have 20 members with 1,000 m2 area of aloe vera plant. The resulted aloe vera leaves were sold to the aloe vera gel drink producer with low prices. The purpose of this activity was to develop aloe vera leaf processing into aloe vera candy- functional food to increase their income and to diversify aloe vera gel processing. The activity used counseling method, practice and assistance to transfer technology in making aloe vera soft candy and the packaging methods. The results showed that the skills of the farmers in making candy were increased, which shown by the bright colors and good textures of the aloe vera soft candy from their practice. The moisture content of the candy appropriate with quality standard and the candy had antioxidative activity. However, it was need assistance in the application of this technology to guarantee for the sustainability as an effort to increase income.